(untitled) - Macdonald, John (Amsterdam ; San Diego, 1993)
The concept of total quality management is designed to improve productivity and employee satisfaction. Based on the ideas of Dr W. Edwards Denning, this technique has been taken up by many of the most successful Japanese companies. This book is aimed at middle management and puts forward ideas that are intended to bring about significant changes in management culture. The authors discuss the principles of quality management, and descibe how the theoretical suggestions made in the book may be put into practice
Keywords: Total quality management